MOTIVASI KERJA, KEPUASAN KERJA, KOMITMEN ORGANISASI, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) - Yuliati Yuliati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
The purpose of this study to analyze the influence of work motivation, job satisfaction on organizational citizenship behavior (OCB) and organizational commitment as implemented in vocational teachers mediasi.Penelitian Gayamsari District Semarang with a sample of 160 teacher.Teknik analysis technique used is Structural Equation Model (SEM) with software AMOS Ver 22.Hasil this study indicate that the causal relationships between variables significantly.The results of this study explains that variabel motivation and commitment is an important factor for improving the quality of learning, because as mental stimulation which is owned by a person in doing voluntary work as guru. But attitude as a form of job satisfaction should be encouraged in the interests of the organization. All of these will be able to bring more students to study in earnest